When leadership fails : individual, group and organizational lessons from the worst workplace experiences - Morris, Lonnie R.; Edmonds, Wendy M. (Emerald Publishing Limited, 2021)
When Leadership Fails is a multidisciplinary resource for researchers and practitioners. As a curated selection of unique, scholar-practitioner reflections from around the world, this collection highlights both the universal impact of leaders behaving badly and the communal triumph that emerges from deconstructing these experiences in aggregate. In addition to expert insight into these leadership and organizational challenges, readers benefit from the application of empirical and theoretical research for analysis and interpretation. Readers will gain a deeper understanding of the individual, group and organizational implications of negative leadership encounters in the workplace. Readers will find value in the immediate application of these lessons to their own careers and organizations.